CSR Pertambangan Batu Bara dalam Perspektif Maqashid Syariah: Analisis Dokumen Program PPM PT Kideco Jaya Agung - Indira, Indira (BISNIS, 2026)
The mining industry supports economic development, yet also generates social and environmental impacts that necessitate the implementation of corporate social responsibility (CSR). From an Islamic perspective, CSR is not merely regulatory compliance, but a moral and spiritual responsibility aligned with maqashid sharia and Islamic business ethics. Existing CSR studies assess regulatory compliance or its impact on the financial performance of mining companies, while maqashid-based assessment of CSR in the coal mining industry remains limited. This study analyzes the CSR practices of PT Kideco Jaya Agung using the maqashid sharia framework, with Islamic business ethics as its operational elaboration, through document analysis of the company's 2024 Annual PPM Report and 2024 Sustainability Report. The findings show that Kideco's PPM fund realization reached IDR 51.05 billion, or 107.47% of the target, indicating alignment with the five dimensions of maqashid sharia, further reflected through Islamic business ethics values, particularly in the sustainable economy sector. However, the environmental management sector received the lowest realization (87.85% of target) despite being most relevant to mining's impact. This study also identifies limitations in the form of an assessment that relies entirely on secondary data with potential affirmative bias, as well as the absence of direct validation from program beneficiaries.